Efecto de la tintura de la Hierba Mora (Solanum Nigrum) para el tratamiento de gingivitis en caninos domésticos Canis Lupus Familiaris - Taipe Defaz, Karina Beatriz (2021)
The objective of this research study was to determine the effect of Blackberry (Solanum Nigrum) tincture as an alternative treatment for bacterial gingivitis in domestic canines (Canis Lupus Familiaris), through topical application. 20 canines were treated at random from the Santa Cruz veterinary clinic, who were subjected to the application of Blackberry tincture in two treatments, after a positive laboratory report of bacteria in the oral cavity. The research technique applied was experimental by means of the t student analysis, two research groups were carried out, each one formed by 10 canines, the treatments with the tincture of Blackberry Herb were applied twice a day, every day for 30 days in T1 and in T2 it was applied twice a day spending one day for 30 days, at day 15- and 30-days new samples were taken to establish the bacterial CFU's. The results obtained from the research concluded that the treatment with the tincture of Blackberry Herb was applied twice a day, every day for 30 days. The results obtained from the research concluded that gram-positive bacteria such as Bacillus spp, Staphylococcus aureus, Staphylococcus spp, coagulase-negative Staphylococcus, Streptococcus spp, beta-hemolytic Streptococcus and gram-negative bacteria Pseudomonas spp had 100% effectiveness, while gram-negative bacteria Escherichia coli had 79% effectiveness at T1, while gram-negative bacteria Escherichia coli and Pseudomonas spp, and gram-positive bacteria such as Bacillus spp, Staphylococcus aureus, Staphylococcus coagulase negative, Staphylococcus spp, Streptococcus beta hemolyticus had 100% effectiveness, with the exception of Streptococcus spp which obtained an effectiveness of 98.75% at T2. Concluding that catechins contain a flavan-3-ol, so it is part of the chemical family of flavonoids that acts as an antioxidant and as a secondary metabolite